(untitled) (Journal of history, 2025)
This article is dedicated to the significance of folk batyrs in the history of Karakalpakstan as a social institution through the activities of Askar Nurymbetov in the lower of the Amu Darya at the beginning of the 20th century. In the research work, to illuminate the life and activities of historical figures in the history of Karakalpakstan, the sources based on the heroic poems, legends, field inscriptions, manuscripts about Askar batyr were analyzed, which were not the focus of historians. A characteristic feature of the folk batyrs in the territory of the left bank of the lower the Amu Darya at the beginning of the 20th century is that their movement did not signify a political movement, and the struggle against the invaders led by Junaidkhan for the defense of the country was a social process aimed at studying in the context of general social history. The new approach and results of consideration in this work can be used for further new approaches and scientific research in the history, historical figures of the late XIX - early XX centuries, as well as in the territory of Central Asia. Furthermore, as there is little information about the activities of Askar Nurymbetov and other historical figures, the materials of this study can be used as open information for those interested in studying the history of Central Asia.